Serum interleukin-8 (IL-8) is elevated in patients with metastatic melanoma and correlates with tumour load - Scheibenbogen, Carmen; Möhler, Thomas; Haefele, Joachim; Hunstein, Werner; Keilholz, Ulrich (Melanoma research, 1995)
It was recently demonstrated that IL-8 is produced by melanoma cell lines and acts as an essential autocrine growth factor. We studied the constitutive production of IL-8 by melanoma cell lines and the serum concentrations in patients with metastatic melanoma. All of 10 melanoma cell lines investigated constitutively produced IL-8 (mean 315 ± 58 pg/10s cells per 24 h. IL-8 was detectable (mean 159 ± 13.1 pg/ml) in the serum of 21 out of 56 patients by an enzyme-linked immunosorbent assay (ELISA; detection limit < 100 pg/ml). There was a significant correlation with tumour load, whereas no correlation with metastatic sites was found. No increased IL-8 levels were seen in healthy controls or patients with metastatic renal cell carcinoma. These results suggest that IL-8 is constitutively produced by melanoma cells in vivo.
Gesehen am 27.11.2025